Growth modulation of angular deformities with a novel constant force implant concept-preclinical results. (April 2021) - Buschbaum, Jan; Freitag, Linda; Slongo, Theodor F.; Zeiter, Stephan; Schütz, Michael; Windolf, Markus
Abstract: Purpose: Varus-valgus deformities in children and adolescents are often corrected by temporary hemi-epiphysiodesis, in which the physis is bridged by an implant to inhibit growth. With standard implant solutions, the acting forces cannot be regulated, rendering the correction difficult to control. Furthermore, the implant load steadily increases with ongoing growth potentially leading to implant-related failures. A novel implant concept was developed applying a controlled constant force to the physis, which carries the potential to avoid these complications. The study aim was to proof the concept in vivo by analyzing the effect of three distinct force levels on the creation of varus deformities. Methods: The proposed implant is made of a conventional cerclage wire and features a twisted coil that unwinds with growth resulting in an implant-specific constant force level. The proximal medial tibial physes of 18 lambs were treated with the implant and assigned to three groups distinct by the force level of the implant (200 N, 120 N, 60 N). Results: The treatment appeared safe without implant-related failures. Deformity creation was statistically different between the groups and yielded on average 10.6° (200 N), 4.8° (120 N) and 0.4° (60 N) over the treatment period. Modulation rates were 0.51°/mm (200 N), 0.23°/mm (120 N) and 0.05°/mm (60 N) and were constant throughout the treatment. Conclusion: By means of the constant force concept, controlled growth modulation appeared feasible in this preclinical experiment. However, clinical trials are necessary to confirm whether the results are translatable to the human pathological situation.